Topical iodophor use in chronic wounds: a literature review (Revista Latino-Americana de Enfermagem, 2007)
This study aimed to do a review of the literature regarding the use of topic iodine and/or compounds in the treatment of chronic wounds. The clinical trials were searched in the Cochrane database. Fourteen (58.3%) among 24 studies fulfilled the inclusion criteria. The articles were analyzed regarding journal and study characteristics and classified into three groups: Iodine versus other topic agents (7/ 50%); Iodine versus different dressings (6/ 42.9%); Iodine versus without Iodine (1/ 7.1%). Favorable results for the use of Iodine or similar product occurred in 50% of the analyzed studies. Six out of 8 trials showed favorable results for healing and infection prevention/ treatment; 4 out of 5 were not favorable when the healing objective was investigated and 1 study for infection treatment showed no favorable result.